Pengaruh Kualitas Komunikasi dan Responsivitas Tenaga Kesehatan Terhadap Kepuasan Pasien di Rumah Sakit Umum Daerah Kabupaten Solok Selatan - Claudya Linanto, Livia; Saputra, Boni (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Public dissatisfaction with public health services in regional hospitals remains a crucial issue, with one cause being the lack of clarity in medical information and slow response times from health workers. This study aims to analyze the effect of effective communication and responsiveness on public satisfaction at the South Solok District Hospital, both partially and simultaneously. Using an associative quantitative approach with the Proportionate Stratified Random Sampling technique, this study involved 398 respondents selected from a population of 70,571 patient visits in 2024. Data were collected through a validated questionnaire and analyzed using multiple linear regression. The results show that effective communication has a positive and significant effect on public satisfaction with a contribution of 24.5% (β = 0.242, p = 0.005), responsiveness has a positive and significant effect with a contribution of 23.7% (β = 0.168, p = 0.048), and simultaneously, both variables contributed 24.9% to public satisfaction (F = 66.826, p = 0.000). These findings have strategic implications for hospital management, including the development of therapeutic communication training programs and improvements to integrated service operational systems.